Malocclusion and prevalence of developmental dental anomalies of form, size, number and eruption in southern Europe - Molina-Solana, Rocío; Solano-Reina, Enrique; Yáñez-Vico, Rosa-María (Journal of Stomatology, 2017)
Aim of the study. To analyze dental anomalies (agenesis, supernumerary teeth, microdontia, transposition, impaction, taurodontism, dilacerations, enamel hypoplasia, dens evaginatus and dens invaginatus) in orthodontic subjects. Material and method. Pretreatment clinical and radiographic records of 379 orthodontic subjects were studied. Results. 22.2% of patients presented at least one dental anomaly. The prevalence in females was statistically significant (chi squared test, p<0.05) compared to males. Conclusions. Congenitally absent teeth and the presence of impacted teeth were the most frequently observed abnormalities. Orthodontic planning and treatment could be improved by bearing in mind the presence of dental anomalies and the relationships between them.